3D TUDE MOVIE SERIES “VIDEO GAME” - Ketut Tri Sutrisna Oka; Padma Nyoman Crisnapati; Made Windu Antara Kesiman; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2013)
The development of multimedia technology is growing rapidly that supports people to maximize their creativity in any purpose. One of the achievements in the development of multimedia technology is 3 dimensional movies so called as 3D animation. Base on the fact that 3D animation film mostly watched by children, researcher developed a 3D animation film with the title of “Video Game”. Moral value that tried to show in this 3D animation film is children should not disregard their study because of video games and they should put studying in first priority as it could brings them to a better future. The method of this research is Diagram Block that described every step in whole process of making “Video Game” 3D animation film. This Diagram Block method consisted of three main processes, 1) Pre Production (idea of the story, writing/synopsis, output format establishment, character designing, supporting image designing, and storyboard making), 2) Production (modeling, texturing , rigging, skinning, action/animation, lighting, and rendering), 3) Post Production (Recording and merging process). The final product of “Video Game” 3D animation film is in DVD format. The goals that expected to be reached of this film development are to bring a good value to support children psychology development and to introduce 3D animation technology to the viewer.